Glucose‐induced LINC01419 reprograms the glycolytic pathway by recruiting YBX1 to enhance PDK1 mRNA stability in hepatocellular carcinoma - Yanfang Liu; Junjiao Song; Qili Shi; Bing Chen; Wenying Qiu; Yizhe Liu; Shenglin Huang; Xianghuo He (Clinical and Translational Medicine)
Abstract Metabolic reprogramming provides the necessary energy for the development of malignant tumours and is emerging as a novel tumour treatment strategy. However, the widespread expression of metabolic enzymes in diverse cell types makes the development of specific drugs that target cancer cells without affecting normal cellular functions challenging. Accumulating evidence has demonstrated the essential roles of long non‐coding RNAs (lncRNAs) in the regulatory network associated with glucose metabolism in tumour cells. The mechanism and therapeutic potential of cancer‐specific lncRNAs in modulating tumour glucose metabolism warrant in‐depth exploration. Here we revealed that glucose‐induced LINC01419 promoted the growth and metastasis of HCC cells by driving metabolic reprogramming. Mechanistically, LINC01419 directly interacted with Y‐box binding protein 1 (YBX1) in the cytoplasm and facilitated its binding to PDK1 mRNA, thus enhancing PDK1 mRNA stability and increasing lactate production. Furthermore, YY1 contributed to the transcriptional activation of LINC01419 in HCC under high‐glucose conditions. Notably, administration of an N‐acetylgalactosamine (GalNAc)‐conjugated siRNA specifically targeting LINC01419 markedly retarded the growth of orthotopic xenograft tumours. These findings provide evidence for an unprecedented regulatory mechanism of LINC01419 involving metabolic reprogramming in human cancer. The newly identified LINC01419/YBX1‐PDK1 axis may represent a promising therapeutic target for HCC. Moreover, GalNAc‐siLINC01419 holds significant potential for clinical application. Key points This study highlights the considerable regulatory role of LINC01419 in the metabolism of HCC. The newly identified LINC01419/YBX1‐PDK1 axis constitutes a valuable target. Hepatic‐specific delivery of GalNAc‐siLINC01419 presents a promising therapeutic strategy for HCC.